Optimal land allocation to crop production in different decision priorities and water availability scenarios: East Azerbaijan province of Iran. Issue 5 (16th April 2022) - Mohammadzadeh, Arash; Vafabakhsh, Javad; Mahdavi Damghani, Abdolmajid; Deihimfard, Reza
ABSTRACT: Optimal cropping pattern of Maragheh-Bonab plain was determined in different decision priorities (from viewpoint of farmers and experts) and annually water availability scenarios [60, 80 and 100 MCM (million cubic meters)/year]. Goal programming model was applied to the optimization of cropping pattern with considering eight goals. In the optimal cropping pattern from viewpoint of farmers, water consumption was reduced compared to existing condition about 42%, 32%, and 3% at 60, 80, and 100 MCM/year scenarios, respectively. While, from viewpoint of experts, this reduction was about 55%, 32%, and 32% for 60, 80, and 100 MCM/year scenarios, respectively. At 60 MCM/year scenario, total net return was calculated lower than the existing cropping pattern about 11% and 45% from the viewpoint of farmers and experts, respectively. However, optimization at 80 and 100 MCM/year scenarios, increased total net return compared to existing condition about 14% and 24% from the viewpoint of farmers and 14% and 14% from the viewpoint of experts, respectively. In the optimal cropping patterns, despite lower water consumption, the amount of net return, economic water productivity, economic energy, and land productivity increased against a decrease in employment, global warming potential, and environmental impacts of pesticides in the whole area.